Polarization, Barriers and Tunneling Times of Some Tautomers of Adenine and Thymine - Marañon, Julio (1979)
The polarization of the radiation involved in some transitions is analysed for the normal and tautomeric forms of adenine and thymine. Tunneling times for some barriers previously reported [1] and equilibrium constants between two isomers for some excited states are also given. The calculations have been made with the CNDO/2-CI method and the results compared with the available experimental data.